1245 | The Effect of Profitability, Solvency, and Company Size on Audit Delay with Auditor Competence as A Moderation Variable - Ricky Bryan D.P. Tampubolon (Publikasi Indonesia, 2025)
This study aims to examine the effect of profitability, solvency, and firm size on audit delay, as well as the role of auditor competence as a moderating variable. The research sample consisted of 122 auditors in Jakarta, serving as senior auditors and supervisors. Data were collected through questionnaires and analyzed using multiple linear regression and moderation testing. The results of the analysis indicate that only solvency has a negative and significant effect on audit delay, while profitability and firm size do not have a significant impact. Auditor competence as a moderating variable also does not significantly moderate the relationship between the three independent variables and audit delay. These findings suggest that efforts to accelerate the audit completion process should focus on improving the auditee’s solvency position and simplifying reporting procedures. Nevertheless, enhancing auditor competence, as well as monitoring profitability and firm size, should remain a priority for continuous improvement.